Spices Fed to Growing Heifers on Bromegrass Result in Increased Gains with Some Effects on Tick Populations - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2020)
Alternative methods to antibiotics/chemical usage in cattle production have been of interest in recent years and essential oils/spices have been promoted to fill this niche. The purpose of this research was to evaluate effect of feeding spices on heifer gains and as a control method for ticks. Eight bromegrass pastures were stocked (March to November) with four heifers per pasture to compare control mineral (CON) to mineral containing spices (SPICE; garlic + proprietary blend of 4 spices). Mineral (4 oz/hd/d) was blended in dried distillers grains (DDGs) and total blend was supplemented daily at 0.5% of heifer body weight. Heifers were weighed on two consecutive days at the start and end of the study and every 28 d. Weekly (first 10 weeks), ticks were counted and removed from every heifer. Average daily gain was increased by 0.15 lb/d with the SPICE mineral, and heifers on SPICE gained 33 lb more over the entire grazing period than heifers on CON. The gain advantage for SPICE was observed within the first four months on supplement and continued through the end of the study. Overall, these heifers had a low tick population (137 total ticks collected). Even so, there was a tendency for SPICE heifers to have more ticks/heifer than CON heifers when measured on weeks 2 and 3, yet at weeks 8 and 10 SPICE heifers tended to have fewer ticks/heifer than CON. SPICE in a mineral blended with DDGs increased heifer gains and appeared, after a minimum of 4 weeks of consumption, to show some repellent effects to ticks.
Keywords: essential oils; ectoparasites; garlic